Keterampilan Pukulan Service Panjang Dan Lob Pada Atlet Klub Persatuan Bulutangkis Cindelaras Tahun 2024 - Nugraha Murdiansyah, Bayu (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2024)
The research is backgroundd because of the ability to atet furtangkis in the union of cindelaras is still often making mistakes while making long service and lob blows. Among the shuttlecocks that fall off the field or the mistakes that often occur are service blows that are too weak to cause shuttlecock hull to fall into the service area. Other than that in a lob punch., Athletes also often make some mistakes like too weak a punch and the shuttlecock's license on a less precise racket that causes the blow to be inaccurate..This research aims to find out how great the beating skills of the long service and lob are in the badminton games on the cindettaras entrails of ponoorogo. This study is a descriptive study of quantity because it gives a description of objects that are carefully examined through the data samples or populations specified in the form of numbers. Method used in this study is a method of surveying.Instruments are tests and measurements of long service tests and clear tests.The subject of research is a 20-estate ponoorogo phallus entangkis cindellaras..Technical data analysis uses descriptive with presentase. Based on the research) 1. The athletes a long service union badminton cindelaras included in category 2 excellent an athlete or as many as 10 of %, good category as many as 40 % athlete or as many as 8, as many as 8 categories enough % athlete or as much as 40, the less % 10 athletes or as many as 2, and the very weak as many as 0 % 0 to athletes.2 ). The ability of a lob athletes unity badminton athletes club cindelaras balong ponorogo included in category 3 very good athletes to as many as 15 %, category 3 athletes or less of as many as 15 %, and the very weak as many as 0 % 0 to athletes. Given the importance of this study please all related parties especially parents are more concerned about the needs/ learning facilities of their sons and daughters so that they can achieve a higher achievement.